Quark Confinement and the Hadron Spectrum IV, Vienna, Austria, 3-8 July 2000 (World Scientific Pub. Co., 2002)
Quantum chromodynamics is generally accepted to be the quantum field theory which describes the strong interactions in elementary particle physics. However, the question of the mechanism responsible for the "confinement" of the color degrees of freedom of quarks and gluons into hadrons still ranks as one of the most interesting open problems in physics. This proceedings volume summarizes the state of the art in this area of research. Mathematically inclined readers will find the articles based on monopoles, vortices, and topology most interesting. Meanwhile, lattice calculations can be performed for many important physical quantities. Their results can be used as guidelines for developing models of quark confinement. These models are indispensable for theoretical physicists performing calculations with the Bethe–Salpeter equation, Dyson–Schwinger equations, effective Hamiltonians, and potential models. The cross-fertilization of all these subfields of research becomes evident from the articles in this book. A few experimental papers are also included